A Good Woman - Steel, Danielle (London Corgi Books, 2009)
Annabelle Worthington, born into a life of privilege, was raised amid the glamour of New York society. But everything changes on a cold April day in 1912, when the sinking of the Titanic alters her world forever.
Keywords: Upper class women